PRAGMATIC FUNCTIONS OF METAPHORS IN THE ENGLISH LANGUAGE (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article examines the pragmatic functions of metaphors in the English language and their role in shaping meaning within discourse. The study focuses on the evaluative, expressive, emotional, and persuasive dimensions of metaphor and explains how metaphor bridges the gap between literal meaning and intended interpretation. Special attention is given to pragmatic theories of metaphor and its communicative impact in literary discourse. The relevance of the topic lies in the growing interest in functional linguistics and pragmatics as modern approaches to language analysis.